The effect of sunflower wax and carnauba wax on the storage stability and sensory evaluation of palm-based chocolate spread - N. A. Mohd Hassim; S. Kanagaratnam; T. K. Tang; N. S. Sofian Seng (Grasas y Aceites)
This study investigates the storage properties and sensory evaluation of palm-based chocolate spreads formulated with sunflower wax (SFW) and carnauba wax (CW) in a wide range of temperatures. Hardness, spreadability and stability assessments of chocolate spreads with 3.5% SFW and 3.5% CW were made over a 24-week storage period. The hardness, spreadability and stability of the chocolate spreads were analyzed by means of Texture Analyzer, observation and LUMiFuge Stability Analyzer, respectively. A sensory evaluation of these chocolate spreads was conducted using a 7-point hedonic scale. The hardness of both chocolate spreads was influenced by low temperatures of 5-10 °C during the storage study. Decreasing and increasing trends were observed for samples stored at 5 and 10 °C, respectively. However, both palm-based chocolate spreads remained spreadable at 5 °C even after 24 weeks of storage. Both chocolate spreads demonstrated stability at 40 °C after 24 weeks of storage. The sensory evaluation revealed that chocolate spread with 3.5% CW was the most widely accepted by sensory panelists. Therefore, chocolate spread with 3.5% CW has the potential to be utilized over a wide range of temperature applications of 5-40 °C.